Therapeutic drug monitoring of selumetinib in pediatrics: a combined LC-MS/MS and LC-HRMS approach - Cafaro, Alessia; Santangelo, Andrea; Barco, Sebastiano; Corsini, Corinna; Bandettini, Roberto; Striano, Pasquale; Diana, Maria Cristina; Cangemi, Giuliana (Frontiers in Pharmacology, 2025)
Neurofibromatosis type 1 (NF1) is a genetic disorder characterized by the development of plexiform neurofibromas (PNs), benign yet potentially debilitating tumors with limited treatment options. Selumetinib, a selective MEK1/2 inhibitor, has emerged as a targeted therapy for symptomatic, inoperable PNs in pediatric NF1 patients. Individual variability in drug metabolism, largely influenced by CYP450-mediated pathways, can affect treatment response. In this study, we describe a novel liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for the quantification of selumetinib in human plasma. The method was validated in accordance with ICH M10 guidelines in the range 1.3–2,000 ng/mL and demonstrated high selectivity, precision and accuracy. Its clinical applicability was assessed in pediatric NF1 patients receiving selumetinib, with measured Ctrough levels ranging from 15.80 to 537.39 ng/mL. To further investigate interindividual pharmacokinetic variability, we applied liquid chromatography–high-resolution mass spectrometry (LC–HRMS) to profile selumetinib metabolites. A total of ten metabolites were identified, including the pharmacologically active N-desmethyl-selumetinib (M8). Metabolite-to-parent ratios (MPRs) suggested notable interpatient differences in metabolic patterns. This combined LC–MS/MS and LC–HRMS strategy provides both precise quantification of selumetinib and insight into patient-specific metabolic profiles. Beyond its analytical strengths, the approach supports therapeutic drug monitoring (TDM) and paves the way for personalized selumetinib dosing.